Sound pressure levels generated at risk volume steps of portable listening devices: types of smartphone and genres of music - Gibbeum Kim; Woojae Han (BMC, 2018)
Abstract Background The present study estimated the sound pressure levels of various music genres at the volume steps that contemporary smartphones deliver, because these levels put the listener at potential risk for hearing loss. Methods Using six different smartphones (Galaxy S6, Galaxy Note 3, iPhone 5S, iPhone 6, LG G2, and LG G3), the sound pressure levels for three genres of K-pop music (dance-pop, hip-hop, and pop-ballad) and a Billboard pop chart of assorted genres were measured through an earbud for the first risk volume that was at the risk sign proposed by the smartphones, as well as consecutive higher volumes using a sound level meter and artificial mastoid. Results The first risk volume step of the Galaxy S6 and the LG G2, among the six smartphones, had the significantly lowest (84.1 dBA) and highest output levels (92.4 dBA), respectively. As the volume step increased, so did the sound pressure levels. The iPhone 6 was loudest (113.1 dBA) at the maximum volume step. Of the music genres, dance-pop showed the highest output level (91.1 dBA) for all smartphones. Within the frequency range of 20~ 20,000 Hz, the sound pressure level peaked at 2000 Hz for all the smartphones. Conclusions The results showed that the sound pressure levels of either the first volume step or the maximum volume step were not the same for the different smartphone models and genres of music, which means that the risk volume sign and its output levels should be unified across the devices for their users. In addition, the risk volume steps proposed by the latest smartphone models are high enough to cause noise-induced hearing loss if their users habitually listen to music at those levels.